TINGKAT ADOPSI PENGGUNAAN PUPUK ORGANIK CAIR URINE KELINCI PADA PETANI PADI DI DUSUN SOROGEDUG KABUPATEN SLEMAN - Adinugra Rimartin, Geraldo; Terunajaya, Erro; Sukadi (Education and Talent Development Center of Indonesia, 2025)
This community service activity aims to increase the adoption rate of liquid organic fertilizer (POC) made from rabbit urine by rice farmers in Sorogedug Hamlet, Madurejo Village, Prambanan Sub-district, Sleman Regency. Through a quantitative descriptive approach, this activity involved 32 farmer members of the farmer group who were the targets of educational interventions in the form of counseling, training, and field demonstrations. The results of the activity showed that the majority of farmers had reached a high level of awareness and interest in the use of POC, although some were still in the trial stage and had not fully adopted it routinely. Factors such as age, formal education, farming experience, land area, and number of family members contributed to variations in the adoption rate. This activity concluded that to encourage the sustainable use of POC, a farmer group-based approach, facilitation of tools and raw materials, and strengthening of adaptive and participatory technical assistance were needed.